Can Monetary Reward Modulate Social Attention? - Lo Gerfo, Emanuele; De Angelis, Jacopo; Vergallito, Alessandra; Bossi, Francesco; Romero Lauro, Leonor Josefina; Ricciardelli, Paola (Frontiers in Psychology, 2018)
Selective visual attention is a primary cognitive function, which allows the selection of the most relevant stimuli in the environment by prioritizing their processing. Several studies showed that this process can be influenced by both social signals, such as gaze direction (i.e., the Gaze Cueing Effect, GCE) and by the motivational valence of gratifying stimuli, such as monetary rewards. The aim of this study was to explore whether GCE could be modulated by a monetary reward. To this end, we created an experiment in which participants performed a gaze cuing task before and after an implicit learning task aiming to induce an association between gaze direction and monetary reward (experimental condition), or after a perceptual task (control condition). Statistical analyses were conducted following both a frequentist and a Bayesian approach. Results supported previous findings showing the presence of the GCE, i.e., faster responses in congruent trials when the target appeared in the gazed-at location. Interestingly, our results did not reveal significant differences among the conditions. Therefore, contrary to what was reported by previous attentional orienting studies with non-social stimuli, monetary reward does not seem to be able to modulate (or interfere with) the orienting of attention mediated by gaze direction as measured by the GCE. Taken together our results suggest that social signals such as gaze direction have a greater impact than monetary reward in orienting selective attention.